Observations of Carbon Nanotube Oxidation in an Aberration-Corrected, Environmental Transmission Electron Microscope - Koh, Ai Leen (2013)
We report the first direct study on the oxidation of carbon nanotubes at the resolution of an aberration-corrected environmental transmission electron microscope (ETEM), as we locate and identify changes in the same nanotubes as they undergo oxidation at increasing temperatures in-situ in the ETEM. Contrary to earlier reports that CNT oxidation initiates at the end of the tube and proceeds along its length, our findings show that only the outside graphene layer is being removed and on occasion, the interior inner wall is oxidized, presumably due to oxygen infiltrating into the hollow nanotube through an open end or breaks in the tube. We believe that this work provides the foundation for much scientific understanding of the mechanism underlying the nanotube oxidation process, as well as guidelines to manipulate their structure or prevent their oxidation.